The Influence of Brand Trust and Brand Image on Post-Regulatory Crisis Purchase Decisions: Extending the Theory of Planned Behavior Among Generation Z - Delisnawati Fikriyah; Muh. Santoso; Moh. Yudi Mahadianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of brand trust and brand image on Generation Z’s purchasing decisions regarding Pinkflash products on Shopee, following the 2024 BPOM issue. This study integrates these two variables within the Theory of Planned Behavior (TPB) framework in the context of the cosmetic regulatory crisis in Indonesian e-commerce, a topic that has received limited research attention. The research employs a quantitative approach with a causal design. Data were collected via a questionnaire from 130 Generation Z respondents in Cirebon who had previously purchased Pinkflash products on Shopee and were aware of the 2024 BPOM issue and were subsequently analyzed using SEM-PLS. The results indicate that brand trust and brand image each have a positive and significant influence on purchase decisions, both in partial and simultaneous effects. Practically, cosmetic companies and e-commerce platforms are advised to enhance transparency regarding BPOM certification and product safety communication to maintain Generation Z consumers’ trust amid the regulatory crisis. This study contributes theoretically by integrating brand trust and brand image into the TPB framework within the context of a post-regulatory crisis in Indonesian e-commerce.